MODELING USING DISCRIMINANT ANALYSIS OPPORTUNITIES DISEASE BOYS AND GIRLS OF PODOLIE WITH ATOPIC DERMATITISDEPENDING ON PECULIARITIES OF THE STRUCTURE AND BODY SIZE - Gunas, I.V.; Gara, A.V. (World of Medicine and Biology, 2014)
In this work we present the results of modeling are set by means of discriminant analysis, the possibility of the disease on limited atopic dermatitis (AD) and various forms of AD boys and girls of Podolie region of Ukraine depending on peculiarities of structure and body size. Were built discriminant model using anthropometric indicators and somatotypological which allow us with a high probability to separate healthy people and patients with limited AD boys or girls. Despite the fairly high percentage of correct classification probability correctly to divide boys and girls using anthropometric indicators and somatotypological various forms of limited AD is questionable, considering on a fairly high values of Wilks lambda statistic. To discriminant models boys most often includes the thickness of skin and fat folds and width of distal epiphysis of long bones of the extremities, and the girls - the thickness of skin-folds and fat obhvatni body size.
Keywords: atopic dermatitis; boys and girls; discriminant models; anthropometry; somatotype